Pengembangan dan Pelatihan Sistem PSB di SMK Ma’arif 1 Temon, Kulon Progo, Daerah Istimewa Yogyakarta - Anief Fauzan Rozi; Agus Sidiq Purnomo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
SMK Ma'arif 1 Temon is a private Vocational High School with 3 expertise programs namely Accounting and Institutional Finance, Clinical and Community Pharmacy, and Software Engineering which is located on Raya Wates Purworejo Street, RT/RW : 27/13, Kaliwangan Hamlet, Temon Wetan Village, Temon District, Kulon Progo Regency, Special Province of Yogyakarta. Even though it has resources and one of the expertise in Information Technology (IT), this school does not yet have a new student admissions system (PSB) and so far, it is still using Google forms. Service activities are carried out by creating an information system that can provide convenience for SMK Ma'arif 1 Temon, as well as making a dashboard to display the PSB recapitulation results. With this community service activity in the form of creating a PSB system, it is hoped that it will facilitate data collection and selection of new student admissions at SMK Ma'arif 1 Temon.